Use of antimicrobials in a specialized cardiology hospital (Revista Contexto & Saúde, 2024)
The management of antimicrobial use has been recognized as a relevant action to mitigate irrational use and the increasing resistance to this class of drugs. Thus, the present study aimed to evaluate the use of antimicrobials by measuring consumption and assessing the appropriateness of treatment regarding indication, dose, and duration, from August to November 2019, in a cardiology specialized hospital. Empirically initiated treatments were also evaluated for their adequacy following culture results and antimicrobial sensitivity testing, with adjustments made as necessary. Additionally, the World Health Organization (WHO) classification was applied, categorizing antimicrobials into Access, Watch, and Reserve (AWaRe) groups based on the impact of their use on microbial resistance and the importance of their appropriate and restricted use. A total of 1558 prescriptions associated with 405 treatments were evaluated. The most commonly used therapeutic classes were combined penicillins, carbapenems, and third-generation cephalosporins. Adequacy in indication was observed in 84.2% of cases. Among these, 88.1% and 90.6% exhibited appropriate dose and treatment duration, respectively. Empirically initiated treatments were predominantly conducted (58.7%) with antimicrobials from the Watch group, followed by the Reserve group (23.5%) and Access group (17.8%). Therapy adjustment was performed in 59% of cases requiring it (57.9%). The results suggest that antimicrobial use should be optimized, aiming to minimize empirical use, favor the use of antimicrobials from the Access category, and promote the adequacy of empirical treatments following culture results.
Keywords: Drug Utilization review; Antimicrobial Stewardship; Drug Resistance Multiple Bacterial